2022
DOI: 10.3390/cancers14246112
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells as a Predictive Biomarker in Resectable Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: In breast, prostate, and other epithelial tumors, circulating tumor cells (CTC) in peripheral blood may predict survival. Our study evaluated the prognostic significance of baseline and postoperative CTC in patients with early non-small cell lung cancer (NSCLC) through a meta-analytic approach. Methods: Prospective studies comparing survival outcomes between positive (CTC+) and negative CTC (CTC−) patients were systematically searched. Primary outcomes were overall (OS) and disease-free survival (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 84 publications
0
11
0
1
Order By: Relevance
“…Recently, CTC has been recognized as a biomarker for postoperative recurrence. [17][18][19] Additionally, the activation of EMT is associated with an increased number of CTC and poor prognosis. 8,9,20 Therefore, it is reasonable to think that the upfront vein division may contribute to a better prognosis because the upfront vein division could prevent CTC from spreading during the surgery; however, upfront vein division was beneficial to the patients without EMT activation in our study and the patients with early-stage in the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CTC has been recognized as a biomarker for postoperative recurrence. [17][18][19] Additionally, the activation of EMT is associated with an increased number of CTC and poor prognosis. 8,9,20 Therefore, it is reasonable to think that the upfront vein division may contribute to a better prognosis because the upfront vein division could prevent CTC from spreading during the surgery; however, upfront vein division was beneficial to the patients without EMT activation in our study and the patients with early-stage in the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cf-DNA, blood components such as CTC, circulating free non-coding RNA and even plasmatic proteins could be of interest in assessing MRD, particularly in association with assays targeting cf-DNA. [35][36][37] Many studies have shown that perioperative detection of CTCs can be integrated into the evaluation of the risk of tumour progression in resected early stage NSCLC. [38][39][40][41][42] However, as there are multiple approaches to CTC detection and the risk of false-negative and false-positive results varies depending on the method used, it is currently difficult to integrate this biomarker into daily practice.…”
Section: Integration Of Multiple Circulating Blood Biomarkers Into Mr...mentioning
confidence: 99%
“…In addition to cf‐DNA, blood components such as CTC, circulating free non‐coding RNA and even plasmatic proteins could be of interest in assessing MRD, particularly in association with assays targeting cf‐DNA 35–37 . Many studies have shown that perioperative detection of CTCs can be integrated into the evaluation of the risk of tumour progression in resected early stage NSCLC 38–42 .…”
Section: Recommendations To Close the Gap Between The Use Of Minimal ...mentioning
confidence: 99%
“… 4 11 CTCs might also be a promising predictive biomarker of mortality and recurrence in early-stage NSCLC, and CTC detection can potentially serve as a tool for minimal residual disease detection in resectable lung cancer after curative surgery. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] CTCs might also be a promising predictive biomarker of mortality and recurrence in early-stage NSCLC, and CTC detection can potentially serve as a tool for minimal residual disease detection in resectable lung cancer after curative surgery. 12,13 CTC was used in molecular detection of human epidermal growth factor receptor 2 (HER2), KRAS, and EGFR mutation in breast, colon, and lung cancer. 14 CTC could be detected long before radiological diagnosis of lung cancer, 15 and therefore was applied in lung cancer screening in highrisk patients in a prospective study but failed to be used as biomarker.…”
Section: Introductionmentioning
confidence: 99%